Asesmen Provinsi DKI Jakarta sebagai Green City dengan Spatial Multi-Criteria Analysis (SMCA) - Pradana, Mohammad Raditia; Wibowo, Adi (Jurnal Pendidikan Geografi Undiksha, 2024)
This research is motivated by the high pressure of urbanization in DKI Jakarta, which has led to a reduction in green open spaces and an increase in air pollution, worsening the quality of the urban environment. These challenges hinder Jakarta's efforts to become a green city, which requires balancing development and environmental preservation. This study aims to analyze Jakarta's suitability as a green city based on urban environmental criteria using a Spatial Multi-Criteria Analysis (SMCA) approach. Using spatial data such as existing green areas, paddy fields, green open spaces, and bike lanes, as well as Landsat 8 satellite imagery, data rasterization and criteria weighting were conducted to produce an SMCA model. The results indicate that most areas in Jakarta show good suitability for a green city, although the measured greenness intensity, indicated by NDVI, tends to be low. A positive correlation between suitability and NDVI shows that areas with higher suitability tend to have greener and denser vegetation. The identification of three areas with the highest suitability provides guidance for decision-makers in optimizing green open space development. These findings can be used to formulate more effective strategies to enhance urban environmental quality and realize the green city concept in Jakarta through a combination of spatial analysis and appropriate policies.